Realice las siguientes ecuaciones:
*(47+ X) = 3 (X + 11)
* 3 (4X – 1) =3 (X + 9)
* 5 (2X – 1) + 3 (X – 2) = 10X – 5

Realice las siguientes ecuaciones:
*(47+ X) = 3 (X + 11)
* 3 (4X – 1) =3 (X + 9)
* 5 (2X – 1) + 3 (X – 2) = 10X – 5
* 3X + 2 (4X- 1) = X + 18
Ayuda….​

1 comentario en «Realice las siguientes ecuaciones:<br />*(47+ X) = 3 (X + 11)<br />* 3 (4X – 1) =3 (X + 9)<br />* 5 (2X – 1) + 3 (X – 2) = 10X – 5»

  1. Respuesta:

    1.   3 (4x -1) = 4 (3x + 3)

    12x – 3 = 3x + 9  

    12x – 3x = 9 + 3

    9x = 12  

    X = 12/9

    X = 4/3

     X = 1, 3

    2. (47 + x) = 3 (x + 11)

    47+ x = 3x + 33

    -3x + x = -47 + 33

    -2x= -14  

    X= – 14/-2

    x=7

    3. 5 (2x – 1) +3 (x- 2) = 10x -5

    10x – 5 + 3x – 6 = 10x – 5

    3x = 7  

    X = 7
    / 3  

    X= 2, 3

    4. 3x + 2 (4x -1) = x +18

    3x + 8x – x = 18 + 2

    10x = 20  

    X = 20/10

         X= 2  

    Explicación paso a paso:

Deja un comentario